2017
DOI: 10.1016/j.chom.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Type VI Secretion across Human Gut Microbiomes Reveals Its Role in Community Composition

Abstract: Summary Although gut microbiome composition is well defined, the mechanisms underlying community assembly remain poorly understood. Bacteroidales possess three genetic architectures (GA1–3) of the type VI secretion system (T6SS), an effector delivery pathway that mediates interbacterial competition. Here we define the distribution and role of GA1–3 in the human gut using metagenomic analysis. We find that adult microbiomes harbor limited effector and cognate immunity genes, suggesting selection for compatibili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 48 publications
6
136
2
Order By: Relevance
“…These include the Esx pathway, prevalent in the phyla Firmicutes and Actinobacteria, and the type VI secretion system (T6SS), which is widespread in the phyla Proteobacteria and Bacteroidetes. Pathogenic bacteria may use these pathways to facilitate invasion of or dominance within polymicrobial infections, whereas for commensal organisms they can dictate compatibility within consortia (Sana et al, 2016; Speare et al, 2018; Verster et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…These include the Esx pathway, prevalent in the phyla Firmicutes and Actinobacteria, and the type VI secretion system (T6SS), which is widespread in the phyla Proteobacteria and Bacteroidetes. Pathogenic bacteria may use these pathways to facilitate invasion of or dominance within polymicrobial infections, whereas for commensal organisms they can dictate compatibility within consortia (Sana et al, 2016; Speare et al, 2018; Verster et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The role of GA1 and GA2 is unknown, but putative effector-immunity pairs (e.g., several evolved PAAR proteins with putative nuclease domains) hint at it being involved in interbacterial competition (Coyne et al, 2016). Supporting this notion, multiple species encode the same effector genes within a single microbiome (Verster et al, 2017). GA1 and GA2 are shared amongst Bacteroides (Coyne et al, 2016;Coyne et al, 2014), whereas GA3 is exclusively found in some Bacteroides fragilis strains (Coyne et al, 2014).…”
Section: T6ss In Resident Gut Microbiotamentioning
confidence: 99%
“…An analysis of infant microbiomes containing B. fragilis is significantly more likely to harbour GA3 structural genes (92%) compared with those of adults (74%), suggesting that GA3 mediates strain level competition early on in gut microbiota development (Verster et al, 2017). As Grampositive bacteria have not been shown to be targets of the T6SS, the decreased abundance of these genera in GA3-containing microbiomes is most likely due to a fitness advantage conferred to GA3 + B. fragilis and not direct action against Firmicutes (Verster et al, 2017). As Grampositive bacteria have not been shown to be targets of the T6SS, the decreased abundance of these genera in GA3-containing microbiomes is most likely due to a fitness advantage conferred to GA3 + B. fragilis and not direct action against Firmicutes (Verster et al, 2017).…”
Section: T6ss In Resident Gut Microbiotamentioning
confidence: 99%
“…Type VI secretion systems (T6SSs), likened to molecular crossbows, are used to transfer toxic effector proteins into target cells and are prevalent within Gram‐negative bacteria including both commensals and AE pathogens. For example, commensal Bacteroidales use T6SSs for competition within the infant microbiome, which has a significant impact on community formation and structure (Verster et al, ). Importantly, enteric pathogens use T6SSs to counteract colonisation resistance by the microbiota.…”
Section: Colonisation and The Regional Microbiotamentioning
confidence: 99%
“…Bacteroidales use T6SSs for competition within the infant microbiome, which has a significant impact on community formation and structure (Verster et al, 2017). Importantly, enteric pathogens use T6SSs to counteract colonisation resistance by the microbiota.…”
Section: The Physical Landscape and Ae Pathogensmentioning
confidence: 99%